Evaluasi Kurikulum Pendidikan Agama Islam: Telaah Tentang Model, Kriteria dan Pendekatan - Inayati, Mahfida; Silvia, Atik; Maimun, Maimun (Multiverse: Open Multidisciplinary Journal, 2023)
This study aims to evaluate the Islamic Religious Education (PAI) curriculum by examining the models, criteria, and approaches used in its implementation. The research background stems from the need to ensure that the PAI curriculum meets educational objectives and remains relevant to contemporary developments. The primary research question is how the current PAI curriculum's models, criteria, and approaches are applied and their impact on student learning. This qualitative research employs data collection techniques such as document analysis, observations, and interviews with teachers and education experts. The findings indicate that the implemented curriculum models are varied, but many are still based on traditional approaches that lack contextual relevance to modern needs. The assessment criteria tend to focus on cognitive aspects rather than affective and psychomotor domains. The approaches used are often less interactive and do not fully support meaningful learning. The conclusion of this study is the necessity to revise the PAI curriculum to integrate more holistic and contextual approaches, and to update assessment criteria to include more comprehensive aspects. This research is expected to contribute to the development of a more effective and relevant PAI curriculum that meets the needs of students in the modern era.